Investigations into the ecology and management of the polyphagous shot hole borer beetle (PSHB, Euwallacea fornicatus) in South Africa - Roberts, Elise (Stellenbosch : Stellenbosch University, 2023)
Thesis (MScConsEcol)--Stellenbosch University, 2023.